BARRIERS TO ENVIRONMENTAL MANAGEMENT IN HOTELS IN KWAZULU- NATAL, SOUTH AFRICA - Sucheran, Reshma (PEOPLE: International Journal of Social Sciences, 2018)
In the last two decades an increasing number of studies have focused on the impacts of tourism development on the environment aimed at the depletion of natural resources, the generation of waste and pollution and general environmental degradation. Consequently, the huge growth in the hotel industry has considerably affected the environment at a global level as the sector consumes large amounts of energy, water and non-durable products. Hotels are therefore now urged to engage in responsible and sustainable environmental management practices. Often hotel managers are keen to engage in responsible environmental practices but are unable to do so due to certain impediments. This article examines the barriers or challenges that are faced in adopting more sustainable and responsible environmental management practices in hotels in KwaZulu- Natal, South Africa. n total, 142 hotels (including hotel chains as one entity) were identified in KwaZulu-Natal and a census approach was adopted, in that all 142 were approached to participate in the study. Sixty hotels responded. Data was collected through a web-based, online survey questionnaire. The findings reveal that hoteliers are faced with a number of barriers in the implementation of environmental management practices. These barriers include lack of knowledge and expertise, lack of resources to implement certain environmental management practices, lack of government assistance, lack of legislation and regulation and high costs. Furthermore, a noteworthy finding is that a number of hotels in KwaZulu-Natal are unaware of the savings potential associated with environmental programmes, that is, the direct benefits to their establishments.